Proteins Breaking Bad: A Free Energy Perspective - Valle-Orero, Jessica; Tapia-Rojo, Rafael; Eckels, Edward C; Rivas-Pardo, Jaime Andrés; Popa, Ionel; Fernández, Julio M (The journal of physical chemistry letters, 2017)
Protein aging may manifest as a mechanical disease that compromises tissue elasticity. As proved recently, while proteins respond to changes in force with an instantaneous elastic recoil followed by a folding contraction, aged proteins break bad, becoming unstructured polymers. Here, we explain this phenomenon in the context of a free energy model, predicting the changes in the folding landscape of proteins upon oxidative aging. Our findings validate that protein folding under force is constituted by two separable components, polymer properties and hydrophobic collapse, and demonstrate that the latter becomes irreversibly blocked by oxidative damage. We run Brownian dynamics simulations on the landscape of protein L octamer, reproducing all experimental observables, for a naive and damaged polyprotein. This work provides a unique tool to understand the evolving free energy landscape of elastic proteins upon physiological changes, opening new perspectives to predict age-related diseases in tissues.